The Implementation of Risk Management in Corporate Asset Optimization: A Case Study of the Building Asset Leasing Plan at PT XYZ - Gultom , Gudiman Franciskus; Sunaryo, Tarsicius; Gunawan, Indra (Universitas Muhammadiyah Pontianak, 2026)
Risk management is crucial in optimizing assets of state-owned enterprises (SOEs) such as PT XYZ. This study analyzes the application of ISO 31000:2018 to a plan for leasing idle assets in the form of office buildings. It identifies inherent risks and the company’s mitigation strategies. The findings show that success depends on regulatory compliance, clear authority, partner due diligence, and integration of internal control systems. Risk mitigation is carried out in a structured manner to ensure good governance and prevent losses. This study may serve as a reference for SOEs in measurable, accountable, and sustainable asset management.